2022
DOI: 10.1515/jpem-2021-0691
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the relationship between environmental endocrine disruptors and precocious puberty in girls

Abstract: Objectives To explore the associations of environmental endocrine disruptors on precocious puberty in girls. Methods This was a case-control study in which 30 girls with precocious puberty and 46 age- and race-matched prepubertal females were enrolled. The concentrations of 10 environment endocrine disruptors (bisphenol A, bisphenol B, butylparaben, propylparaben, ethvlparaben, methylparaben, mono-butyl phthalate, mono-2-ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Moreover, regarding P, the average E2 concentration of girls with central PP was 18.50 ± 21.97 pg/mL, while that of girls with incomplete PP was 5.21 ± 5.50 pg/mL. This result was expected since signs of PP are usually the clinical feature of a premature activation of the HPG axis, which leads to E2 release in females resulting in a high concentration of this hormone in their blood [1,[56][57][58], but could also be due to other external factors such as EDC exposure [8,59]. The comparison between E2 concentrations found in the present study with the physiological E2 concentrations during the pre-pubertal period showed that the average E2 concentrations in the serum of girls in the present study were within the range of the physiological values (<27 pg/mL, data provided by the Regina Margherita Children hospital, Table S1 in Supplementary Materials 2).…”
Section: E2 Concentrationsmentioning
confidence: 80%
“…Moreover, regarding P, the average E2 concentration of girls with central PP was 18.50 ± 21.97 pg/mL, while that of girls with incomplete PP was 5.21 ± 5.50 pg/mL. This result was expected since signs of PP are usually the clinical feature of a premature activation of the HPG axis, which leads to E2 release in females resulting in a high concentration of this hormone in their blood [1,[56][57][58], but could also be due to other external factors such as EDC exposure [8,59]. The comparison between E2 concentrations found in the present study with the physiological E2 concentrations during the pre-pubertal period showed that the average E2 concentrations in the serum of girls in the present study were within the range of the physiological values (<27 pg/mL, data provided by the Regina Margherita Children hospital, Table S1 in Supplementary Materials 2).…”
Section: E2 Concentrationsmentioning
confidence: 80%
“…Endocrine disruptors are ubiquitous in the environment, and might also be risks for CPP. In a casecontrol study, Zhou et al compared urinal metabolites and serum hormones of 30 precocious puberty girls with 46 ageand race-matched prepubertal females, and confirmed the association of CPP with phthalate esters exposure (68). Ubiquitously present bisphenol A is another threat to female CPP, possibly through Kiss1 activation in ARC (69, 70).…”
Section: Treatment and Prevention Strategies For Cppmentioning
confidence: 97%
“…Those associations were stronger in pubertal children ( 31 ). In our previous study, we observed steroid hormone changes in the blood samples of PP girls, including those of hydrocortisone, 11-deoxycortisol, corticosterone, deoxycorticosterone, and pregnenolone, and also found that EDC exposure may affect the metabolism of steroid hormones in the body ( 32 ). In a similar study, steroid hormone biosynthesis was also identified as an enriched pathway for DEMs of CPP girls ( 33 ).…”
Section: Discussionmentioning
confidence: 93%